Reconceptions in Philosophy & Other Arts & Sciences - Goodman, Nelson; Elgin, Catherine Z. (London Routledge, 1988)
Nelson Goodman's work develops themes in philosophy of science, mind, art, and language. Born in Massachusetts, he was educated at Harvard University and had an early career as an art dealer. After military service during World War II, he chose the academic life and taught at the University of Pennsylvania and Brandeis University before returning to Harvard in 1968. Goodman's early work grows out of logical positivism. His paradox presents a difficulty for inductive logic. It is developed by showing that an empirical statement can be expressed by more than one set of words and that its' degree of confirmation can depend on the words used to express it---not solely on its content or the supporting evidence. Scientific method thus intersects the philosophy of language. On this basis, Goodman develops a sophisticated nominalism (a view stressing the power of language to determine meaning), which remains solidly within the analytic tradition. His philosophy of language also develops themes of construction and simplicity. Goodman's later work contains an original treatment of representation. In asking how an original can be represented in perception, language, or art, he argues that there is no straightforward relation between the original and its representation. Understanding a photograph as a representation, for example, is neither simple nor intuitive. Representations, to be understood as such, must be interpreted instead within a network of more or less conventional rules.
Keywords: 20th Century (1901-2000); Philosophy; Esthetics